PROBLEMS OF FORMING AND MANAGING THE MIGRATION ATTRACTIVENESS OF UKRAINIAN REGIONS IN THE CONDITIONS OF MARTIAL STATE (Coordinates of Public Administration, 2025)
The article examines the specific features of forming and managing the migration attractiveness of Ukraine’s regions under martial law. The full-scale war has triggered large-scale internal population displacement and a significant shift in spatial mobility, which has generated new requirements for regional capacity to receive, retain, and integrate internally displaced persons (IDPs). The study substantiates the need to update approaches to assessing migration attractiveness in a context where security factors dominate and the socio-economic situation remains unstable.An original Migration Attractiveness Index model is proposed, comprising five key components: security, economic opportunities, infrastructure and housing, social services, and administrative support. Using the western regions of Ukraine as a case study, the methodology is tested and regions with the highest potential to accommodate IDPs are identified. The findings show that Lviv and Ivano-Frankivsk oblasts demonstrate the highest levels of migration attractiveness, whereas Ternopil, Volyn, and Rivne oblasts require additional resources and support programmes.The article outlines the principal challenges of migration governance, including infrastructure overload, deficiencies in the IDP registration and tracking system, security risks, and difficulties related to the long-term integration of displaced persons. A comprehensive approach to enhancing regional migration attractiveness is proposed, encompassing the development of housing and social infrastructure, improvement of data collection systems, deeper cooperation with international organizations, and the implementation of strategic planning instruments.